2010
DOI: 10.1002/sce.20421
|View full text |Cite
|
Sign up to set email alerts
|

Argument‐Driven Inquiry as a way to help students learn how to participate in scientific argumentation and craft written arguments: An exploratory study

Abstract: This exploratory study examines how a series of laboratory activities designed using a new instructional model, called Argument-Driven Inquiry (ADI), influences the ways students participate in scientific argumentation and the quality of the scientific arguments they craft as part of this process. The two outcomes of interest were assessed with a performance task that required small groups of students to explain a discrepant event and then generate a scientific argument. Student performance on this task was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
241
0
35

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 300 publications
(280 citation statements)
references
References 49 publications
(72 reference statements)
4
241
0
35
Order By: Relevance
“…Based on the research, many of the learning process that occurs in the arguments either in individual or group activities involve thinking deeper and integrate new knowledge with students' prior knowledge [2]. So learning that involves arguing that was built by individuals and groups can support an understanding of students in scientific concepts.…”
Section: Argumentation For Science Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the research, many of the learning process that occurs in the arguments either in individual or group activities involve thinking deeper and integrate new knowledge with students' prior knowledge [2]. So learning that involves arguing that was built by individuals and groups can support an understanding of students in scientific concepts.…”
Section: Argumentation For Science Learningmentioning
confidence: 99%
“…Modern reform in science education is to accentuate the context, activities, and scientific communication. Scientific communication is very important because it is considered able to improve understanding and changing the understanding of science [2]. They also concluded that provides…”
Section: Introductionmentioning
confidence: 99%
“…This was because of they found new terms or concepts in science class. It could be barrier to greater student"s achievement [8], included starting argumentations. Because of that, students have to read a lot of books to build their understanding of knowledge.…”
Section: Students' Argumentation Skillmentioning
confidence: 99%
“…Morerover, implementing the argument-based learning method is not easy because there are challenges from teacher, curriculum goals, and evaluation [6]. Considering that fact, it can be seen that there is a gap between science education and learning fact because the argumentation process is disregarded [8]. This situation doesn"t give any good impact for the science education development because students" high potential is disregarded as well.…”
Section: Introductionmentioning
confidence: 99%
“…Argumentation can be in a form of discussion activity between teacher-student and student-student. It is science learning about investigation of statement and evidence logically [17]. Students who lack of reasoning skill are incapable in delivering their views of something.…”
Section: Introductionmentioning
confidence: 99%